PENGARUH KECERDASAN EMOSIONAL DAN REGULASI EMOSI TERHADAP RESILIENSI AKADEMIK SISWA SMA - Siregar, Julinda; Yuliati, Yuyun; Barnas Komaruddyi, Yudi; Kurniawati, Iis; Wulan Trisnawati, Inne; Rohayati, Dede; Sri Rahayu, Novi; Insani, Sri; Hajar Birlanti, Shofina; Sumarni, Yunita; Budi Angantyo, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic resilience is an important ability that enables students to cope with various pressures and challenges encountered during the learning process. However, not all students possess adequate resilience, making it necessary to identify factors that contribute to its development. This study aimed to examine the influence of emotional intelligence and emotion regulation on the academic resilience of senior high school students. The research employed a quantitative approach with a causal correlational design. The sample consisted of 45 tenth-grade students from a senior high school in Sumedang Regency selected through purposive sampling. Data were collected using emotional intelligence, emotion regulation, and academic resilience questionnaires based on a Likert scale. Data analysis was conducted using descriptive statistics, Pearson correlation, and multiple linear regression with IBM SPSS Statistics. The results revealed that emotional intelligence had a positive and significant relationship with academic resilience (r = 0.667; p < 0.001), and emotion regulation also had a positive and significant relationship with academic resilience (r = 0.550; p < 0.001). Multiple regression analysis indicated that emotional intelligence significantly predicted academic resilience (β = 0.553; p < 0.001), whereas emotion regulation did not show a significant partial effect (β = 0.162; p = 0.102). Simultaneously, emotional intelligence and emotion regulation significantly influenced academic resilience, contributing 45.8% of the variance (R² = 0.458). These findings highlight the importance of developing students’ emotional competencies to strengthen academic resilience in school settings.